Information society in Russian Federation - VINARCHIK, Aleksandr (Journal of Education, Technology and Computer Science, 2016)
This article is devoted to the actual topic of the Information Society in Russian Federation. In the present conditions we can’t imagine our life without opportunities, which gives us the information society. From the quality of the development of this sector depends largely on the level of development of society as a whole.